COVID-19 and Nurse-Sensitive Indicators: Using Performance Improvement Teams to Address Quality Indicators During a Pandemic. Issue 1 (January 2021) - Stifter, Janet; Sermersheim, Emily; Ellsworth, Mary; Dowding, Erin; Day, Elizabeth; Silvestri, Karen; Margwarth, Jessica; Korkmaz, Kerem; Walkowiak, Nicole; Boudreau, Lisa; Hernandez, Laura; Harbert, Bryce; et al.
Abstract : Background: Nurse-sensitive quality indicators have historically been used as a metric of nursing care quality in health care organizations. Problem: At our academic medical center, critically ill COVID-19 patients led to a dramatic change in the organizational standard of care resulting in an increase in nurse-sensitive health care–associated infections. Approach: Nursing performance improvement teams provided the structure for development of innovative strategies implemented in real time by our frontline clinicians to address the quality and safety issues found with these elevated health care–associated infections. Outcomes: A new COVID-19 CLABSI (central line–associated bloodstream infection) Tip Sheet and a Prone Positioning Kit for HAPI Prevention are strategies developed to address quality of care issues experienced with the COVID-19 patients. Conclusions: Deployment of these innovative practice strategies has led to a decline in health care–associated infections and instituted a new care standard for the COVID-19 patients. Abstract : Supplemental Digital Content is Available in the Text.